New optimal modular Sidon sets. (2017) - Shao, Zehui; Deng, Fei; Liang, Meilian; Xu, Xiaodong; Zou, Mingjun
Sidon set and its related problems including modular Sidon set have many applications in information theory and communication system. They have been widely studied in radio frequency selection, radio antennae placement and error correcting codes. In this paper, we establish a backtracking algorithm with pruning techniques to construct modular Sidon sets. By using master-slave parallel model, 50 new optimal modular Sidon sets are constructed.